CORE ETHICAL VALUES PENDIDIKAN KARAKTER BERBASIS NILAI-NILAI ISLAM - Samsudin, Agus (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2022)
The purpose of this paper is to determine the core ethical values ​​of character education based on Islamic values. This research method uses the library research method, using the content analysis method in the form of descriptive-analytic, with sources consisting of articles, journals, and books related to the topic of writing. The results of this paper conclude that according to Aan Hasanah Islam is a conceptual framework in character education by understanding the concept of human beings who have physical, spiritual and interpretive elements, as well as the concept of Fitrah which prioritizes religious potential and tends to the truth. With these two concepts, character education that is developed is character education based on the development of a person's religious potential. By using a moral perspective in character education, Islam functions as a core ethical value, a core ethical value as a source of individual behavior. There are several core ethics that are derived as values ​​that can be taught through educational methodology.